2005
DOI: 10.2139/ssrn.871102
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Transaction Pricing on the Adoption of Electronic Payments: A Cross-Country Comparison.

Abstract: Pricing should speed up the substitution of low cost electronic payments for expensive paper-based transactions and cash. But by how much? Norway has explicitly priced individual payment transactions and rapidly shifted to electronic payments while the Netherlands has experienced the same shift without direct pricing. Controlling for differences between countries, we estimate the incremental effect of pricing on the shift to electronic payments. If users strongly value the improved convenience or security of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 6 publications
1
17
0
1
Order By: Relevance
“…During the past 10 years, the academic interest in payment studies has grown considerably. The most recent interesting empirical studies include Bolt et al (2005), , , HBD (2002), Van Hove et al (2005), Hyytinen and Takalo (2004), Klee (2004), Stavins (2001), Schuh and Stavins (2006) and Zinman (2005). The picture emerging from these studies with regard to payment choice and personal characteristics are in line with our results for Dutch consumers.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…During the past 10 years, the academic interest in payment studies has grown considerably. The most recent interesting empirical studies include Bolt et al (2005), , , HBD (2002), Van Hove et al (2005), Hyytinen and Takalo (2004), Klee (2004), Stavins (2001), Schuh and Stavins (2006) and Zinman (2005). The picture emerging from these studies with regard to payment choice and personal characteristics are in line with our results for Dutch consumers.…”
Section: Introductionsupporting
confidence: 87%
“…Cross-subsidisation of the retail payment system by surcharging other banking services also distorts the equilibrium demand for these services. Humphrey et al (2001), and Bolt et al (2005) show that consumers are sensitive to explicit pricing of payment services and that this can indeed stimulate consumers to pay more often electronically, reducing the social costs of the retail payment system.…”
Section: Practice and Consequences Of Tariff Structure Of Dutch Pos Pmentioning
confidence: 99%
“…In the rare instances where comprehensive data are available for comparison, usually cash is excluded; see the studies by Bolt, Humphrey, and Uittenbogaard (2008) and the Federal Reserve System (2013). However, new research is revealing the emergence of an ironic consensus:…”
Section: Introductionmentioning
confidence: 99%
“…In Ching and Hayashi (2010), the only measure of use was a consumer's preferred payment instrument, and no estimation of either the extensive or intensive margins of payment use were included. Bolt, Humphrey, and Uittenbogaard (2008) estimated the use of electronic payments in Norway and the Netherlands as a function of relative prices to find that pricing has a small effect on payment choice. They therefore concluded that "convenience, safety, and other nonprice attributes of different payment instruments" play an important role in influencing payment behavior.…”
Section: Payments Usementioning
confidence: 99%